(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
Nursing education involves a practice-oriented curriculum focusing on theoretical learning and psychomotor skills (Eyikara & Baykara, 2017). Nurses are trained to practice their profession efficiently and competently to the alarming rate of the increasing complexity of patient cases. This situation led to a cumulative demand for student nurses to be prepared to face various situations. Nursing simulation with return demonstration in skills laboratories is defined as a controlled and safe environment for nursing students to learn and refine their psychomotor skills (Goswami et al., 2021). In contrast, experiential laboratory experiences provide undergraduate nursing students with hands-on opportunities to integrate knowledge and clinical skills (Tsusaki et al., 2022). This helps nursing students to unite and value knowledge, develop technical and interactive skills, and develop disciplines and responses for thinking and reflection (Kim, Park, &Shin, 2016). This rich learning opportunity for students will combine theory with practice while making real-time clinical judgments in an environment that poses no threat to patients. Clinical skills demonstration is crucial for student nurses to improve their ability and expand their knowledge in a practical healthcare setting. Integrating clinical experience with the nursing education curriculum prepares students to transition into the professional nurse’s role (Wang, Lee, &Espin, 2019). According to the study findings of Msosa et al. (2022), demonstrations, return demonstrations, practice sessions, and resources contribute effectively to learning. Meanwhile, hasty demonstrations, limited practice time, and inadequate resources affect learning negatively. Moreover, real-life experience must be provided, for their insights will never be obtained from textbooks and theories (Ning, 2022). Going through the learning process, there will always be a possibility or instances that student nurses encounter problems or difficulties during their clinical duties. This study used the qualitative approach, a precisely descriptive research design. Specifically, Husserlian Phenomenology is utilized. The philosophical underpinnings of it were that of the lived human experience. The study was conducted at Union Christian College (UCC) School of Health Sciences. The eight participants of the study were chosen through purposive sampling. Inclusion criteria included all nursing students at Union Christian College who have skills in laboratory courses at any given age and both genders. The exclusion criteria are those who still need to meet the inclusion criteria and are unwilling to be interviewed. The researchers were the primary data-gathering instruments for this study. An unstructured interview served as a springboard for the primary data collection of the study. The researchers began the study by submitting it to the protocol of the ethical research panel of the College of Nursing, wherein deliberation is conducted for approval of the study. They need an authorization letter approved by the Dean of the School of Health Sciences at UCC. After this, the researchers seek permission from the Ethics Review Board of Union Christian College (UCC). Before the interview, the World Health Organization (WHO) informed consent was presented to the participants. The interview lasted 30 to 35 minutes per participant and was optional. The researchers conducted the interviews face-to-face and recorded them using an audio recorder on their cellphones with the participants’ permission. The interview lasted until the saturation point was reached. The researchers used pseudonyms to protect the participants’ privacy, and confidentiality and safety were ensured in every piece of information they provided. The study’s findings revealed four (4) primary themes: Diamond in the Rough, Quarrying in the Deep, Faceting the Diamond, and Unbreakable Diamond, which sums up into a phenomenon, “Untamed Diamond.” Diamond in the Rough: This theme presents students’ experiences exploring various nursing skills. It included their anxiousness, nervousness, and encounters with the new medical terminologies. Likened to exploring a diamond beneath the grounds, they need to prepare and gear themselves. The anxiousness surrounding them at the beginning of their demonstration revealed fear and nervousness that may interrupt their pursuit. They were like rare uncut diamonds; they were not perfect from the start of their return demonstration, but they strived to perform. Quarrying in the Deep: This theme reveals how the nursing students Study hard for their return demonstration. Likened to quarry in the deep, they must burn the midnight oil or stay up late to learn and keep quarrying new knowledge. As they continue learning, they meet difficulties that can interfere with acquiring their skills, such as lack of equipment, unstable internet connectivity, and realizations of whether or not to continue in their profession. Faceting the Diamond: This theme portrays the students’ experience with their various learning strategies and exposure to the instructor’s teaching strategies. They were compared to faceting the diamond because they were shaped and polished to bring out their brilliance. They were molded to be sophisticated and ready to endure pressure to develop themselves. They were like well-rounded diamonds that had various facets of experience and knowledge. They must undergo challenges, indulge in different learning styles, and be educated in various teaching styles. Unbreakable Diamond: This theme showed the students’ confidence, positivity, determination, and learning application. They can be likened to the diamond’s strong and resilient structure. It signified their hard work and dedication to mastering their skills in the laboratory. Despite the challenges that may come their way, students remain confident, positive, determined, and able to apply what they have learned. The participants’ blazing self-determination gave them the strength to continue their journey toward success. Nursing students’ experiences with their skills in laboratory learning were associated with a diamond in the rough. This showed how nursing students started to undergo their skills laboratory return demonstration; they were likened to a rough diamond, unpolished, and did not sparkle at the start. As students, they do not start refined and perfect in their performance. However, with enough learning and consistent engagement in their return demonstration, they renounced an earnest attitude toward their increasing value. Like a carat, their worth will increase as they continue to improve and strive harder under pressure. Above all, throughout the process, the participants continued to withstand hardships and remained positive and firm in every aspect of their lives as nursing students. They strived harder to reach their goal, and in times of struggle, they believed in themselves and that with great sacrifice comes opportunity and achievements. Like a natural diamond, they did well under the circumstances; they gained higher value as they were cut and put under pressure. They were a diamond, precious and rare.